Association of food consumption and physical activity with metabolic syndrome according to central obesity status in Indonesian adults: A cross-sectional study - Permatasari, Mayang Januarti; Syauqy, Ahmad; Noer, Etika Ratna; Pramono, Adriyan; Tjahjono, Kusmiyati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
Background: Previous studies have reported that the risk of metabolic syndrome differs between obese and non-obese individuals based on food consumption and physical activity.Objective: This study aims to analyze differences in the association of food consumption and physical activity with the incidence of metabolic syndrome in individuals with and without central obesity.Materials and Methods: This cross-sectional study examined individuals aged 19 to 64 years using Riskesdas 2018 data. Sample characteristics, including smoking habits, alcohol consumption, food consumption, physical activity, anthropometric data, clinical data, and biochemical data were collected for univariate, bivariate, and multivariate analyses. Logistic regression was used as a multivariate analysis to investigate the association of food consumption and physical activity with the risk of metabolic syndrome in individuals with and without central obesity. Results: In this study, individuals with and without central obesity significantly increased risk of metabolic syndrome (p<0.05) due to consuming nearly all kinds of unhealthy foods (sweet foods, savory foods, fatty/cholesterol-rich/fried foods, grilled foods, processed meat/chicken/fish, soft drinks/carbonated drinks, energy drinks, and instant noodles/other instant foods). However, only individuals without central obesity who frequently consume seasonings (OR=1.519, 95% CI: 1.241-1.859) have a significant association with an increased risk of metabolic syndrome. Meanwhile, only individuals with central obesity who often consume sugary drinks (OR=1.315, 95% CI: 1.132-1.529) are significantly associated with an increased risk of metabolic syndrome. In addition, inadequate consumption of fruits and vegetables as well as lack of physical activity also significantly increase the risk of metabolic syndrome in individuals with and without central obesity (p<0.05).Conclusion: Only the consumption of seasonings and sugary drinks shows a different relationship to the risk of metabolic syndrome in individuals with and without central obesity.